Pengendalian Risiko Kecelakaan Kerja Menggunakan Metode Job Sefety Analysis Pada Pekerjaan Glass Cleaning Di PT. KSO APS ISS - Jawad, Aod Abdul; Nurrokhman, Agus (Universitas Teuku Umar, 2024)
The KSO APS ISS company is one of the cleaning companies in Indonesia which is located in the Tangerang Banten area. In carrying out its work cycle operations, it uses a lot of chemicals, heavy level machines and potentially dangerous B3 materials. During work there are various potential and risk factors that cause work accidents and work-related illnesses. Company performance, especially in terms of work productivity, is often disrupted as a result of ignoring occupational safety and health rules in carrying out work. The aim of this research is to find out what factors cause work accidents and how to prevent or control risks in Glass Cleaning work in order to reduce the occurrence of work accidents. This research uses the Job Safety Analysis method. The Job Safety Analysis method is a way to look at work techniques and find dangers from the design of machines, equipment, materials, climate and work processes needed by workers to do their work. The research design used is qualitative which is used to describe explanations related to hazard identification, risk evaluation and risk control in glass cleaning work. The results of research using the JSA identification method contained no extreme and high risk jobs, 3 medium risk jobs and 5 low risk jobs.